The effect of glycaemic index of high carbohydrate diets consumed over 5 days on exercise energy metabolism and running capacity in males - Hamzah, S.; Higgins, S.; Abraham, T.; Taylor, P.; Vizbaraite, D.; Malkova, D. (Journal of Sports Sciences, 2009)
The aim of this study was to determine whether rates of total fat and carbohydrate oxidation and endurance capacity during running conducted in the fasted state are influenced by the glycaemic index (GI) of high carbohydrate diets consumed over 5 days. Nine healthy males performed three treadmill runs to exhaustion at 65 % of maximum oxygen uptake (VO2max): after a habitual diet (control trial), after 5 days on a high carbohydrate/high glycaemic index diet, and after 5 days on a high carbohydrate/low glycaemic index diet in randomized counterbalanced order. No significant differences in rates of fat and carbohydrate oxidation, concentrations of plasma insulin, glucose, non-esterified fatty acids and glycerol, or time to exhaustion were observed between the high carbohydrate/high glycaemic index and high carbohydrate/low glycaemic index trials. Compared with the control trial, the concentration of plasma glycerol and rate of fat oxidation were lower (P < 0.05) and the rate of carbohydrate oxidation higher (P < 0.05) in both the high carbohydrate/high glycaemic index diet and high carbohydrate/low glycaemic index trials during the run to exhaustion. In conclusion, the extent by which a high carbohydrate diet consumed over 5 days reduces rate of fat oxidation during subsequent running exercise in the fasted state is not influenced by the glycaemic index of the diet.